FUNCTIONS AND CLASSIFICATION INTER-SUBJECT RELATIONS - Alizhanov Dilmurod Azamzhon ugli (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the need to implement interdisciplinary connections in the educational process, as well as reveals the essence and content of the function and classification of interdisciplinary connections in teaching school subjects.